A Ferroelectric Aminophosphonium Cyanoferrate with a Large Electrostrictive Coefficient as a Piezoelectric Nanogenerator. Issue 3 (12th December 2022) - Vijayakanth, Thangavel; Sahoo, Supriya; Kothavade, Premkumar; Bhan Sharma, Vijay; Kabra, Dinesh; Zaręba, Jan K.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy
Abstract: Hybrid materials possessing piezo‐ and ferroelectric properties emerge as excellent alternatives to conventional piezoceramics due to their merits of facile synthesis, lightweight nature, ease of fabrication and mechanical flexibility. Inspired by the structural stability of aminophosphonium compounds, here we report the first A3 BX6 type cyanometallate [Ph2 ( i PrNH)2 P]3 [Fe(CN)6 ] (1 ), which shows a ferroelectric saturation polarization ( Ps ) of 3.71 μC cm −2 . Compound 1 exhibits a high electrostrictive coefficient ( Q33 ) of 0.73 m 4 C −2, far exceeding those of piezoceramics (0.034–0.096 m 4 C −2 ). Piezoresponse force microscopy (PFM) analysis demonstrates the polarization switching and domain structure of 1 further confirming its ferroelectric nature. Furthermore, thermoplastic polyurethane (TPU) polymer composite films of 1 were prepared and employed as piezoelectric nanogenerators. Notably, the 15 wt % 1 ‐TPU device gave a maximum output voltage of 13.57 V and a power density of 6.03 μW cm −2 . Abstract : A ferroelectric Iron (III) cyanometallate complex stabilized by organo‐aminophosphonium cations was synthesized and utilized for efficient piezoelectric energy harvesting and storage applications.